Tendency and readiness of the enterprise shift decision among natural rubber smallholder farmers In Padang Terap, Kedah / Nor Ariza Jaafar - Jaafar, Nor Ariza (Faculty of Plantation and Agrotechnology, 2015)
Agricultural sector plays an important role in Malaysia's economic development. But nowadays, the economic situation for commodity crop such as rubber so challenging to rubber producer. Poor rubber price gives big impact to rubber tappers because most of them rely on rubber crops as sources of income. It is important to evaluate the tendency and readiness of enterprise shift decision among rubber smallholder possibility whether to change to other crops. The study was conducted in several communities at Padang Terap, Kedah. Primary data with structured questionnaire were collected from 286 respondents of smallholder using random sampling. Data collected were analyses using multiple regression analysis and descriptive statistics. The result indicates majority 162 rubber plantation owners (113.4%) disagree to shift from rubber enterprise to other agricultural enterprises, medium with 36 respondents (25.2%), and 88 respondents (61.6%) indicated decision to remain in rubber production. Regression analysis revealed that readiness and tendency had significant effect on enterprise shift decision (P<O.Ol). This study significant to rubber tappers to choose whether to shift from rubber production to selected crops or not to search agricultural enterprise which may gives high profit and generates more income. The study also can be useful guide to RISDA to improve the utilization level of rubber management practices among rubber farmers and find out how to avoid rubber tappers making decisions to shift from rubber cultivation to other selected crops.